PROFIL PELAJAR PANCASILA SEBAGAI UPAYA MEWUJUDKAN KARAKTER SISWA DALAM PERSPEKTIF THOMAS LICKONA - Wiwin Kurniyanti; Wahyu Warastuti; Yustina Neny Hastuti; Bambang Sumardjoko; Endang Fauziati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to review the Pancasila Student Profile as an effort to realize student character from Thomas Lickona's perspective. The method used in this research is a library research approach, where library research can be interpreted as a series of activities relating to methods of collecting library data, reading and taking notes and processing research materials. The Pancasila Student Profile is a character development framework based on Pancasila values. The six dimensions of the Pancasila Student Profile are in line with the three key elements of character education according to Thomas Lickona: knowing the good, loving the good, and doing the good. This research explains how the Pancasila Student Profile can be implemented in learning to help students develop strong character. This implementation can be done through various methods, such as project-based learning, collaborative learning, and authentic assessment. The results of this research explain several challenges and strategies in implementing the Pancasila Student Profile. These challenges include a lack of understanding about character education, lack of resources, and a school culture that is not yet supportive. Strategies to overcome these challenges include increasing outreach and education about character education, strengthening resources, and building a supportive school culture.